Sir Edmund Head : A Scholarly Governor - Kerr, D. G. G. (Donald Gordon Grady), 1913-1976 (Book collections on Project MUSE., 1954)
A century ago, in 1854, Sir Edmund Head became governor general of Canada. His earlier career as Oxford don, chief Poor Law commissioner during the "hungry forties," and lieutenant-governor of New Brunswick, had prepared him to succeed Lord Elgin in this senior post in the British colonial service. Combining the outlook and training of a scholar with a long administrative experience in difficult posts, Head had a clear insight into British North American problems, and was able to guide British and Canadian politicians toward their solution in the creation of the new Dominion of Canada. Later, as Governor of the Hudson's Bay Company, he carried negotiations for the transfer of the Company's territories to the verge of conclusion before his sudden death in 1868. Neglected until recently by Canadian historians, the significance of the work of one of Britain's greatest colonial administrators is only now beginning to be appreciated. Professor Kerr's biography creates a lively and convincing picture of Head and colonial life at a critical period. Based on careful research among the public documents of the period, and making use as well of Head's private letters to close friends in England and North America, it is the first full-scale treatment available of this philosophic and capable governor whose influence on Canadian national development was so important